Protection of the Rights of the Old Age Security Fund in Indonesia - Rahmatiah Hl; Muhammad Reski S (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2022)
The main thing that became the source of the problems when the issuance of the Minister of Manpower Regulation No. 2 of 2022, which is in article 3 which contains the payment of JHT benefits that can only be given when they reach the age of 56 years. The government seems to be less sensitive to this situation, because the reality is that for workers when they are laid off, the disbursement of JHT funds is used to survive, because it is very unfair if the government makes this regulation from the eyes of middle and upper class workers, where this old-age guarantee fund is indeed they use as capital when they have entered retirement. The research used is normative juridical research, so the approach is astatute approach. The results of the study illustrate that there are two forms of legal protection for participants in the old-age insurance program at BPJS Ketenagakerjaan for arrears in payment of contributions by employers, namely preventive and repressive legal protection. Preventive legal protection is based on Government Regulation Number 60 of 2015 concerning Amendments to Government Regulation Number 46 of 2015 concerning the Implementation of the Old Age Security Program. Structuring the national social security system is indeed necessary to ensure the welfare of the people from youth to old age. However, the road to an orderly system cannot be done rashly, in haste, and bypasses the protection of the majority of workers who need it most, especially in the midst of the current situation. The delay is required for several years, not just three months as currently stated in the regulation.